2019
DOI: 10.1101/696823
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RPS28B mRNA acts as a scaffold promoting cis-translational interaction of proteins driving P-body assembly

Abstract: P-bodies (PBs) are cytoplasmic mRNA-protein (mRNP) granules conserved throughout eukaryotes which are implicated in the repression, storage and degradation of mRNAs. PB assembly is driven in part by proteins with self-interacting and low-complexity protein domains.Non-translating mRNA is also required for PB assembly, however no studies to date have explored whether particular mRNA transcripts are more critical than others in facilitating PB assembly. A previous genome-wide microscopy screen in yeast revealed … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…In our hands, all so far tested 3 0 UTRs controlled protein activity without affecting protein abundance, indicating that this function of 3 0 UTRs is widespread. This has also been suggested by others (Fernandes 2019;Ribero 2019). 3' UTR-independent interactors 3' UTR-dependent interactors Figure 3.…”
Section: Mass Spectrometry Identifies 3 0 Utr-independent and 3 0 Utrsupporting
confidence: 84%
“…In our hands, all so far tested 3 0 UTRs controlled protein activity without affecting protein abundance, indicating that this function of 3 0 UTRs is widespread. This has also been suggested by others (Fernandes 2019;Ribero 2019). 3' UTR-independent interactors 3' UTR-dependent interactors Figure 3.…”
Section: Mass Spectrometry Identifies 3 0 Utr-independent and 3 0 Utrsupporting
confidence: 84%
“…Notably, a recent study that deleted 3′UTR sequences in several cytokine genes found similar discrepancies between reporter-based assays and gene expression from native contexts (Zhao et al, 2017). Although our data indicate that p53 abundance regulation is 3′UTR-independent, the 3′UTR may still have important functions possibly through control of protein localization or protein activity as has been shown for other proteins (Berkovits and Mayr, 2015; Moretti et al, 2015; Terenzio et al, 2018; Lee and Mayr, 2019; Fernandes and Buchan, 2020; Bae et al, 2020; Kwon, 2020; Mayr, 2019).…”
Section: Discussionmentioning
confidence: 53%
“…In vitro, a small amount of RNA initially promotes protein droplet formation and afterwards begins dissolving the droplets once the concentration of the RNA reaches a threshold [ 76 , 77 ]. RNAs change physical properties of condensates (i.e., viscosity), augment granule assembly in vitro and in vivo [ 13 , 44 , 67 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ], determine the three dimensional structure of granules in an RNA concentration-dependent manner [ 49 , 85 ], and can even instruct the morphology of granules by their ability to engage in intermolecular RNA-RNA interactions [ 86 ].…”
Section: Formation Of Rna Granules: the Role Of The Rnamentioning
confidence: 99%